2017
DOI: 10.1097/mou.0000000000000395
|View full text |Cite
|
Sign up to set email alerts
|

Current treatment of pelvic organ prolapse correlated with chronic pelvic pain, bladder and bowel dysfunction

Abstract: In conclusion, it has to be recognized that women bothered by these symptoms should be examined for POP and appropriately advised for possibility of cure by pelvic floor surgery after careful selection. VIDEO ABSTRACT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
15
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 38 publications
2
15
0
4
Order By: Relevance
“…The present data also support the findings of previous studies [11][12][13][14][15][16][17][18][19][20][21] showing that OAB symptoms in women with POP significantly improve, and even resolve, after anatomical POP surgical correction, with a durable response in OAB symptom improvement and/or cure observed at 2 years after surgery. Interestingly, in women with ≥stage 2 POP, further delineation of the severity of POP had no significant influence on postoperative OAB symptom cure rates.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The present data also support the findings of previous studies [11][12][13][14][15][16][17][18][19][20][21] showing that OAB symptoms in women with POP significantly improve, and even resolve, after anatomical POP surgical correction, with a durable response in OAB symptom improvement and/or cure observed at 2 years after surgery. Interestingly, in women with ≥stage 2 POP, further delineation of the severity of POP had no significant influence on postoperative OAB symptom cure rates.…”
Section: Discussionsupporting
confidence: 92%
“…At baseline, 70% of patients had at least one moderate or severe OAB‐related symptom, with 50% reporting symptoms that were severe. In the current literature, the rate of coincidence of POP and OAB varies between 37% and 91% , while the prevalence of OAB in women without POP has been reported to be 4–9% . This provides some epidemiological evidence for the coexistence of POP and OAB, and therefore deserves further study.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…9 CPP may be caused by POP due to the laxity of the supporting and/or suspending connective tissue structures. 33 Surgical treatment for POP may improve pelvic pain and quality of life. 34 , 35 Following surgery for POP, some authors have reported an improvement in sexual function, while others have failed to find any difference or have shown a deterioration in sexual function.…”
Section: Discussionmentioning
confidence: 99%
“…We were very pleased to receive endorsements of the main thrust of our paper by authors of the letter to the editor and that of the other authors quoted [ 1 – 4 ], that symptoms of overactive bladder (OAB), urgency, frequency, urgency incontinence, nocturia, are surgically curable in women with pelvic organ prolapse.…”
mentioning
confidence: 99%